Maf nuclear oncoprotein recognizes sequences related to an AP-1 site and forms heterodimers with both Fos and Jun. - Kataoka, K (1994)
The v-maf oncogene, identified from AS42 avian retrovirus, encodes a nuclear bZip protein. To elucidate the molecular mechanism of cell transformation induced by this oncogene, we determined the specific binding sequences of its product. Maf protein recognized two types of relatively long palindromic consensus sequences, TGCTGACTCAGCA and TGCTGACGTCAGCA, at roughly equal efficiency. The middle parts of these Maf-binding sequences completely match with two binding sequences for AP-1 transcription factor, i.e., phorbol 12-O-tetradecanoate-13-acetate (TPA)-responsive element (TRE) and cyclic AMP responsive element, suggesting partial overlapping of the target genes for Maf and AP-1. Furthermore, Maf efficiently formed heterodimers with the components of AP-1, Fos and Jun, through their leucine zipper structures, and these heterodimers show binding specificities distinct from those for Maf-Maf and Jun-Jun homodimers. Thus, a multiple combination of the dimers should generate a greatly expanded repertoire of transcriptional regulatory potential. DNA data base search for the Maf-binding consensus sequences suggested that some of the TRE-like cis elements reported previously may actually be the targets for Maf family proteins or their heterodimers with other bZip proteins.